Keterbatasan Kerangka Keamanan dalam Menangani Kekerasan Berbasis Gender Online Transnasional di Indonesia - Nadine Imanuela Pratiwi Sitaniapessy (Jurnal Ilmu Sosial dan Humaniora, 2026)
This article examines a gap in Indonesia's legal response to Kekerasan Berbasis Gender Online (KBGO): although domestic instruments — Law No. 12 of 2022 on Sexual Violence Crimes (UU TPKS) and the Electronic Information and Transactions Law (UU ITE, as amended by Law No. 1 of 2024) — have criminalized specific acts of online gender-based violence, neither law treats KBGO as a security threat in the structural sense. Using a dual analytical lens of Transnational Organized Crime (TOC) theory and Feminist Security Studies (FSS), bridged by the human security paradigm, this article argues that Indonesia has criminalized KBGO without securitizing it. Drawing on the Copenhagen School's distinction between normal politics and securitization, the analysis shows that UU TPKS frames electronic sexual violence as a list of individualized, punishable acts rather than a recurring structural pattern, while UU ITE's public-order orientation and documented jurisdictional weaknesses leave it unable to confront KBGO as an organized, networked, and increasingly transnational phenomenon. This conceptual gap is reflected empirically in a 40.8% year-on-year rise in reported KBGO cases despite the existence of dedicated criminal provisions. The article concludes that criminalization, while a necessary legislative achievement, is an insufficient response on its own, and that closing the gap requires recognizing KBGO as a structural security concern warranting anticipatory institutional capacity rather than reactive prosecution alone.